Odpowiedź:
[tex]a) \: 1 - \frac{1}{4} = \frac{4}{4} - \frac{1}{4} = \frac{3}{4} [/tex]
[tex]1 - \frac{7}{10} = \frac{10}{10} - \frac{7}{10} = \frac{3}{10} [/tex]
[tex]b) \: 1 - \frac{6}{20} = \frac{20}{20} - \frac{6}{20} = \frac{14}{20} [/tex]
[tex]1 - \frac{25}{100} = \frac{100}{100} - \frac{25}{100} = \frac{75}{100} [/tex]
[tex]c) \:2 - \frac{5}{6} = 1 \frac{6}{6} - \frac{5}{6} = 1 \frac{1}{6} [/tex]
[tex]3 - \frac{1}{3} = 2 \frac{3}{3} - \frac{1}{3} = 2 \frac{2}{3} [/tex]
[tex]d) \: 4 - \frac{6}{10} = 3 \frac{10}{10} - \frac{6}{10} = 3 \frac{4}{10} [/tex]
[tex]5 - \frac{1}{7} = 4 \frac{7}{7} - \frac{1}{7} = 4 \frac{6}{7} [/tex]
Pozdrawiam.